Replacement of reinforced concrete by bamboo in social dwellings in Ecuador, using moment connections (Gaceta Técnica, 2021)
This research article is based on a theses theme developed in Ecuador, which main objective was to replace social houses built in reinforced concrete with bamboo in order to decrease construction costs and to be collaborative with environment. Normally, structural nodes for bamboo buildings are considered pinned between beams and columns according to structural analysis normative, but nevertheless, in construction, nodes present kind of continuity, due to the use of concrete or mortar inside the bamboo elements, also, reinforcing steel. In this research, an analytical model for one kind of node were simulated in order to demonstrate the bending moments transfer, and also, demonstrated the viability of the substitution of the reinforced concrete by bamboo in social dwellings in Ecuador. Results indicate that all joints transmit bending moments.
Keywords: bamboo buildings; bamboo connections; bamboo nodes; bamboo joints